2021
DOI: 10.4028/www.scientific.net/kem.884.184
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sorghum Varieties on Digestibility and Nitrogen Balance of Complete Feed in Goats

Abstract: This study aimed to determine the effect of sorghum varieties (Brown Midrib Resistance and Super-2) on digestibility and nitrogen balance. Twelve female Bligon goats with an average body weight of 24.33±2.83 kg were divided into 3 groups of treatments with 4 replications, following a Completely Randomized Design (CRD) one-way pattern, T1 = complete feed based on fresh of Pennisetum purpureum as a control, T2 = complete feed based on silage of sorghum Brown Midrib Resistance (BMR), and T3 = complete feed based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The total excretion of PD in TMR based on sorghum silage (ISS and LSS) was low due to the lower feed consumption than FNG. According to Rahayu et al [ 13 ], based on the results of this study, Bligon goats given TMR based on Napier grass fresh forage resulted in a higher nutrient feed intake than BMR or super-2 of sorghum silage. High feed intake positively correlated with increased total excretion of PD and vice versa.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…The total excretion of PD in TMR based on sorghum silage (ISS and LSS) was low due to the lower feed consumption than FNG. According to Rahayu et al [ 13 ], based on the results of this study, Bligon goats given TMR based on Napier grass fresh forage resulted in a higher nutrient feed intake than BMR or super-2 of sorghum silage. High feed intake positively correlated with increased total excretion of PD and vice versa.…”
Section: Discussionmentioning
confidence: 57%
“…The higher ADWG in FNG was in correlation with feed intake. Rahayu et al [ 13 ] reported that Bligon goats given TMR based on Napier grass fresh forage resulted in a higher nutrient intake than TMR based on BMR or super-2 sorghum silage. This significant variation in BW was affected by the variation in concentrate level and nutrient content in the TMR [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations